Aesthetic Humility: A Kantian Model. Issue 526 (17th May 2022) - Matherne, Samantha
Abstract: Unlike its moral and intellectual counterparts, the virtue of aesthetic humility has been widely neglected. In order to begin filling in this gap, I argue that Kant's aesthetics is a promising resource for developing a model of aesthetic humility. Initially, however, this may seem like an unpromising starting point as Kant's aesthetics might appear to promote aesthetic arrogance instead. In spite of this prima facie worry, I claim that Kant's aesthetics provides an illuminating model of aesthetic humility that sheds light not only on the self- and other-directed attitudes it involves, but also on how aesthetic humility can serve as a corrective to the vices of aesthetic arrogance and aesthetic servility. In addition to revealing the ways in which Kant's aesthetics prizes humility rather than arrogance, I aim to show that the Kantian model of aesthetic humility can enrich our understanding of humility more generally and contribute to the on-going effort in aesthetics to analyse specific aesthetic virtues and vices.